PENINGKATAN KETERAMPILAN GURU SEKOLAH DASAR DALAM MENGGUNAKAN TEKNOLOGI INFORMASI DAN KOMUNIKASI MELALUI PELATIHAN - Madiyono Madiyono Madiyono (UNIVERSITAS BENGKULU, 2016)
This research aims to improve the skill of teacher in the use of Information Comunication and Technology. The research study design is a research method school (PTS). The subject is teachers of state elementary School 08 Ketahun District of North Bengkulu. Research shows in the first cycle, the level of ability of participants of the workshop using ICT is 43,34 %, capable of using Microsof Word, Microsof Excel and Microsof Power Point, and the second cycle level workshop participant’s ability to use ICT is 73,34 %. Based on the results of the study coaching principals in improving the profesionalism of the filed of skill in the use of ICT greatlyneeded.Keywords: skill, information comunication and technology